Gel sodium ion battery electrolyte as well as preparation method and application thereof

The preparation of a gel sodium ion battery electrolyte with a polyolefin ester molecular copolymer addresses the thermal and mechanical weaknesses of solid polymer electrolytes, enhancing the electrochemical performance and cycle stability of sodium-ion batteries through a cross-linking process.

CN119253054APending Publication Date: 2025-01-03BEIJING INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411686135.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-24
Publication Date
2025-01-03

Smart Images

  • Figure CN119253054A_ABST
    Figure CN119253054A_ABST
Patent Text Reader

Abstract

The invention discloses a gel sodium-ion battery electrolyte and a preparation method and application thereof, and belongs to the technical field of sodium-ion batteries, the preparation method comprises the following steps: adding a polyvinylidene fluoride-hexafluoropropylene copolymer into an organic solvent, and stirring to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer solution; adding ethoxylated trimethylolpropane triacrylate, an initiator and an olefinic acid ester monomer into the polyvinylidene fluoride-hexafluoropropylene copolymer solution, and stirring at room temperature to obtain a mixed solution; carrying out a cross-linking reaction on the mixed solution under ultraviolet irradiation, and curing the obtained reaction solution into a transparent film; and drying the transparent film in vacuum, and soaking in an electrolyte to obtain the polybasic olefin acid ester molecule copolymerization gel electrolyte. The gel sodium-ion battery electrolyte disclosed by the invention has good thermal stability, mechanical strength performance and ionic conductivity, and the electrochemical performance and cycling stability of a sodium-ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a gel sodium ion battery electrolyte and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have gradually become a powerful alternative to lithium-ion batteries due to their abundant resources, low cost and high safety. At present, research work is mainly focused on the development and design of positive and negative electrode materials for sodium-ion batteries. The electrolyte provides a stable migration environment for sodium ions between the positive and negative electrodes. It is an important component of the battery and affects the safety and electrochemical performance of the battery. The development of solid electrolytes to replace flammable liquid electrolytes can effectively reduce the hidden dangers of electrolyte leakage. At the same time, solid electrolytes can inhibit the growth of sodium dendrites during charging and discharging, reduce the risk of internal short circuits in the battery, and increase the cycle life of the battery. Therefore, the development and design of new sodium-ion solid electrolytes are of great significance to the development of sodium-ion battery technology and secondary battery energy storage.

[0003] In the research of sodium ion solid electrolytes, solid polymer electrolytes have attracted attention due to their advantages such as light weight, high safety, low cost, and good flexibility. However, the existing solid polymer electrolytes have insufficient thermal stability, low mechanical strength, and low ion conductivity, which leads to poor electrochemical performance and short cycle life of sodium ion batteries, which seriously limits the overall performance of solid sodium ion batteries. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for preparing a gel sodium ion battery electrolyte. The gel sodium ion battery electrolyte prepared by the preparation method has good thermal stability, mechanical strength and ionic conductivity, and improves the electrochemical performance and cycle stability of the sodium ion battery.

[0005] A second object of the present invention is to provide a gel sodium ion battery electrolyte.

[0006] The second purpose of the present invention is to provide an application of a polyolefin ester molecular copolymer gel sodium ion electrolyte.

[0007] In order to achieve one of the above purposes, the present invention adopts the following technical solution:

[0008] A method for preparing a gel sodium ion battery electrolyte, the preparation method comprising:

[0009] Step S1, adding polyvinylidene fluoride-hexafluoropropylene copolymer to an organic solvent, stirring at a temperature of 40 to 80° C. for 2 to 6 hours to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer solution;

[0010] Step S2, adding ethoxylated trimethylolpropane triacrylate, an initiator and an olefin acid ester monomer to the polyvinylidene fluoride-hexafluoropropylene copolymer solution, stirring at room temperature for 25 to 35 minutes to obtain a mixed solution;

[0011] Step S3, subjecting the mixed solution to a cross-linking reaction for 0.5 to 2 hours under ultraviolet irradiation, and then curing the obtained reaction solution into a transparent film;

[0012] Step S4, vacuum drying the transparent film at a temperature of 60-80° C. for 8-12 hours, and then immersing the film in an electrolyte having a molar volume concentration of 0.8-1.2 mol / L for 8-12 hours to obtain a polyolefin ester molecular copolymer gel electrolyte.

[0013] Furthermore, in the step S1, the mass ratio of the polyvinylidene fluoride-hexafluoropropylene copolymer to the organic solvent is 1:5-12.

[0014] Furthermore, in step S1, the organic solvent is one of N-methylpyrrolidone, acetonitrile, dimethylacetamide, dimethylformamide and dimethyl sulfoxide.

[0015] Furthermore, in the step S2, the mass ratio of the polyvinylidene fluoride-hexafluoropropylene copolymer, ethoxylated trimethylolpropane triacrylate, initiator and olefin acid ester monomer is 0.083-10:1:0.005-0.5:0.2-1.

[0016] Further, in the step S2, the olefin acid ester monomer is n-butyl methacrylate or benzyl methacrylate;

[0017] In the step S2, the initiator is one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and methyl benzoylformate.

[0018] Furthermore, in step S3, the wavelength of the ultraviolet light is 365 nm.

[0019] Furthermore, in step S4, the absolute pressure of the vacuum drying is less than 200 Pa, preferably 160-180 Pa.

[0020] Further, in step S4, the solute in the electrolyte is one of sodium perchlorate, sodium hexafluorophosphate and sodium bistrifluoromethanesulfonate;

[0021] The solvent in the electrolyte is one or more of PC, EC, DEC and FEC.

[0022] In order to achieve the second objective above, the present invention adopts the following technical solution:

[0023] A polyolefin acid ester molecular copolymer gel sodium ion electrolyte is prepared by the above-mentioned preparation method.

[0024] In order to achieve the third objective above, the present invention adopts the following technical solution:

[0025] An application of a polyolefin acid ester molecular copolymer gel sodium ion electrolyte, wherein the polyolefin acid ester molecular copolymer gel sodium ion electrolyte is prepared by the above-mentioned preparation method;

[0026] The polyolefin acid ester molecular copolymer gel sodium ion electrolyte is used as a polymer electrolyte of a secondary sodium ion battery.

[0027] In summary, the technical solution of the present invention has the following technical effects:

[0028] The invention uses ultraviolet light polymerization (i.e., cross-linking reaction) at room temperature to in-situ solidify different olefin ester monomers containing carbon-carbon double bonds on a three-dimensional polymer framework of a polyvinylidene fluoride-hexafluoropropylene copolymer, cross-link olefin ester molecules containing carbon-carbon double bonds and having different main chain structures, and form a dense semi-interpenetrating three-dimensional network structure, thereby enhancing the thermal stability and mechanical strength of the gel electrolyte and inhibiting the growth of dendrites on the electrode electrolyte interface; at the same time, the three-dimensional polymer framework on the dense semi-interpenetrating three-dimensional network structure provides a stable ion channel, and the abundant n-butyl groups, olefin groups and ester groups on the three-dimensional polymer framework promote the dissociation of sodium salt in the electrolyte, enhance the absorption capacity of the gel electrolyte for the electrolyte, improve the sodium ion migration number of the gel electrolyte, and ensure the cycle performance of the gel sodium ion battery; the polyolefin ester molecular copolymer gel electrolyte of the invention has good thermal stability, mechanical strength and ionic conductivity, and ensures the electrochemical performance and cycle stability of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 1(a), 1(b) and 1(c) are microscopic morphology images of the polyolefin ester molecular copolymer gel electrolytes prepared in Examples 1, 2 and 3, respectively;

[0031] Figure 2 Thermogravimetric analysis test results of the polyolefin ester molecular copolymer gel electrolyte prepared in Examples 1 to 3;

[0032] Figure 3 The stress-strain test results of the polyolefin ester molecular copolymer gel electrolyte prepared in Examples 1 to 3;

[0033] Figure 4 The test results of AC impedance spectroscopy of the polyolefin ester molecular copolymer gel electrolyte prepared in Examples 1 to 3;.

[0034] Figure 5 This is a graph showing the constant current charge and discharge test results of a button-type sodium ion battery assembled with the polyolefin ester molecular copolymer gel electrolyte prepared in Examples 1 to 3. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Embodiment 1:

[0037] Step S1, adding polyvinylidene fluoride-hexafluoropropylene copolymer to N-methylpyrrolidone at a mass ratio of 1:10, stirring at a temperature of 50° C. for 2 hours to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer solution.

[0038] Step S2, adding ethoxylated trimethylolpropane triacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone and n-butyl methacrylate to the polyvinylidene fluoride-hexafluoropropylene copolymer solution, stirring at room temperature for 30 minutes to obtain a mixed solution.

[0039] Among them, the mass ratio of polyvinylidene fluoride-hexafluoropropylene copolymer, ethoxylated trimethylolpropane triacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone and n-butyl methacrylate is 1:1:0.01:0.334.

[0040] Step S3, transferring the mixed solution into a polytetrafluoroethylene mold, irradiating it with an ultraviolet lamp with a wavelength of 365 nm for 1 hour to complete the cross-linking reaction, and then curing the reaction solution into a transparent film.

[0041] Step S4, under vacuum conditions with an absolute pressure of 180 Pa and at a temperature of 60° C., the transparent film is vacuum dried for 12 hours, and then immersed in an electrolyte with a molar volume concentration of 1.0 mol / L for 12 hours to obtain a polyolefin ester molecular copolymer gel electrolyte.

[0042] The solute of the electrolyte is sodium perchlorate and the solvent is PC.

[0043] The microscopic morphology of the polyolefin ester copolymer gel electrolyte prepared in this example is as follows: Figure 1 (a) The electrolyte membrane has a flat surface and can fully contact with the electrode in the sodium ion battery, ensuring stable charge and discharge cycle performance of the battery.

[0044] Embodiment 2:

[0045] Step S1, adding polyvinylidene fluoride-hexafluoropropylene copolymer to acetonitrile at a mass ratio of 1:5, stirring at a temperature of 40° C. for 4 hours to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer solution.

[0046] Step S2, adding ethoxylated trimethylolpropane triacrylate, 1-hydroxycyclohexyl phenyl ketone and benzyl methacrylate to the polyvinylidene fluoride-hexafluoropropylene copolymer solution, stirring at room temperature for 25 minutes to obtain a mixed solution.

[0047] The mass ratio of polyvinylidene fluoride-hexafluoropropylene copolymer, ethoxylated trimethylolpropane triacrylate, 1-hydroxycyclohexyl phenyl ketone and benzyl methacrylate is 0.083:1:0.005:0.2.

[0048] Step S3, transferring the mixed solution into a polytetrafluoroethylene mold, irradiating it with an ultraviolet lamp with a wavelength of 365 nm for 30 minutes to complete the cross-linking reaction, and then curing the reaction solution into a transparent film.

[0049] Step S4, under vacuum conditions with an absolute pressure of 190 Pa and a temperature of 70° C., the transparent film is vacuum dried for 8 hours, and then immersed in an electrolyte with a molar volume concentration of 0.8 mol / L for 8 hours to obtain a polyolefin ester molecular copolymer gel electrolyte.

[0050] The solute of the electrolyte is sodium hexafluorophosphate and the solvent is EC.

[0051] The microscopic morphology of the polyolefin ester copolymer gel electrolyte prepared in this example is as follows: Figure 1 (b) The electrolyte membrane has a flat surface and can fully contact with the electrode in the sodium ion battery, ensuring stable charge and discharge cycle performance of the battery.

[0052] Embodiment 3:

[0053] Step S1, adding polyvinylidene fluoride-hexafluoropropylene copolymer to dimethylacetamide at a mass ratio of 1:12, stirring at a temperature of 80° C. for 6 hours to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer solution.

[0054] Step S2, adding ethoxylated trimethylolpropane triacrylate, methyl benzoylformate and benzyl methacrylate to the polyvinylidene fluoride-hexafluoropropylene copolymer solution, stirring at room temperature for 35 minutes to obtain a mixed solution.

[0055] The mass ratio of polyvinylidene fluoride-hexafluoropropylene copolymer, ethoxylated trimethylolpropane triacrylate, methyl benzoylformate and benzyl methacrylate is 10:1:0.5:1.

[0056] Step S3, transferring the mixed solution into a polytetrafluoroethylene mold, irradiating it with an ultraviolet lamp with a wavelength of 365 nm for 2 hours to complete the cross-linking reaction, and then curing the reaction solution into a transparent film.

[0057] Step S4: vacuum-dry the transparent film at 80°C for 10 hours under a vacuum condition of 160 Pa absolute pressure, and then immerse it in an electrolyte solution with a molar volume concentration of 1.2 mol / L for 10 hours to obtain a polyolefin ester molecular copolymer gel electrolyte, wherein the solute of the electrolyte solution is sodium bistrifluoromethanesulfonate and the solvent is DEC.

[0058] The microscopic morphology of the polyolefin ester copolymer gel electrolyte prepared in this example is as follows: Figure 1 (c) The electrolyte membrane has a flat surface and can fully contact with the electrode in the sodium ion battery, ensuring stable charge and discharge cycle performance of the battery.

[0059] The polyolefin ester copolymer gel sodium ion electrolyte prepared in Examples 1 to 3 was subjected to thermogravimetric analysis using a METTLERTOLEDO TGA / DSC 3+ synchronous thermal analyzer. The test results are shown in Figure 2 The polyolefin ester molecular copolymer gel sodium ion electrolyte prepared in Examples 1 to 3 does not experience rapid mass loss at a temperature below 350° C., and has no obvious thermal decomposition or combustion phenomenon, which proves its good thermal stability.

[0060] The polyolefin ester molecular copolymer gel sodium ion electrolyte prepared in Examples 1 to 3 was subjected to stress-strain test using an INSTRON 5982 testing machine. The test results are shown in Figure 3 The polyolefin ester molecular copolymer gel sodium ion electrolyte prepared in Examples 1 to 3 can maintain structural integrity without breaking under stress conditions below 14.6 MPa, demonstrating its good mechanical strength.

[0061] The polyolefin ester molecular copolymer gel sodium ion electrolyte prepared in Examples 1 to 3 and the stainless steel blocking electrode were assembled into a CR2032 type symmetrical battery. The battery was tested for AC impedance spectroscopy at room temperature. The test results are shown in Figure 4 The polyolefin ester molecular copolymer gel sodium ion electrolyte prepared in Examples 1 to 3 exhibits low impedance at room temperature, proving that it has high ionic conductivity, ensuring its ability to quickly conduct sodium ions in sodium ion batteries.

[0062] The polyolefin ester molecular copolymer gel sodium ion electrolyte prepared in Examples 1 to 3 was respectively assembled with metallic sodium and commercial sodium vanadium phosphate positive electrode into a CR2032 type battery with a structure of sodium negative electrode / polyolefin ester molecular copolymer gel sodium ion electrolyte / sodium vanadium phosphate positive electrode. The battery was subjected to constant current charge and discharge test using a LAND battery test system at room temperature. The test results are shown in FIG. Figure 5 The sodium ion battery assembled with the polyolefin ester molecular copolymer gel sodium ion electrolyte prepared in Examples 1 to 3 can maintain a high discharge specific capacity and coulombic efficiency during a long period of charge and discharge cycles. Based on this, the sodium ion battery prepared using the polyolefin ester molecular copolymer gel sodium ion electrolyte prepared in Examples 1 to 3 has a good cycle life.

[0063] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing a gel sodium ion battery electrolyte, characterized in that: The preparation method comprises: Step S1, adding polyvinylidene fluoride-hexafluoropropylene copolymer to an organic solvent, stirring at a temperature of 40 to 80° C. for 2 to 6 hours to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer solution; Step S2, adding ethoxylated trimethylolpropane triacrylate, an initiator and an olefin acid ester monomer to the polyvinylidene fluoride-hexafluoropropylene copolymer solution, stirring at room temperature for 25 to 35 minutes to obtain a mixed solution; Step S3, subjecting the mixed solution to a cross-linking reaction for 0.5 to 2 hours under ultraviolet irradiation, and then curing the obtained reaction solution into a transparent film; Step S4, vacuum drying the transparent film at a temperature of 60-80° C. for 8-12 hours, and then immersing the film in an electrolyte having a molar volume concentration of 0.8-1.2 mol / L for 8-12 hours to obtain a polyolefin ester molecular copolymer gel electrolyte.

2. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of the polyvinylidene fluoride-hexafluoropropylene copolymer to the organic solvent is 1:5-12.

3. The preparation method according to claim 2, characterized in that: In the step S1, the organic solvent is one of N-methylpyrrolidone, acetonitrile, dimethylacetamide, dimethylformamide and dimethyl sulfoxide.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S2, the mass ratio of the polyvinylidene fluoride-hexafluoropropylene copolymer, ethoxylated trimethylolpropane triacrylate, initiator and olefin acid ester monomer is 0.083-10:1:0.005-0.5:0.2-1.

5. The preparation method according to claim 4, characterized in that: In the step S2, the olefin acid ester monomer is n-butyl methacrylate or benzyl methacrylate; In the step S2, the initiator is one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and methyl benzoylformate.

6. The preparation method according to claim 5, characterized in that: In step S3, the wavelength of the ultraviolet rays is 365 nm.

7. The preparation method according to claim 6, characterized in that: In the step S4, the absolute pressure of the vacuum drying is less than 200Pa.

8. The preparation method according to claim 7, characterized in that: In the step S4, the solute in the electrolyte is one of sodium perchlorate, sodium hexafluorophosphate and sodium bis(trifluoromethanesulfonate); The solvent in the electrolyte is one or more of PC, EC, DEC and FEC.

9. A polyolefin ester molecular copolymer gel sodium ion electrolyte, characterized in that: The polyolefin acid ester molecular copolymer gel sodium ion electrolyte is prepared by the preparation method described in any one of claims 1 to 8.

10. An application of a polyolefin ester molecular copolymer gel sodium ion electrolyte, characterized in that: The polyolefin ester molecular copolymer gel sodium ion electrolyte is prepared by the preparation method described in any one of claims 1 to 8; The polyolefin acid ester molecular copolymer gel sodium ion electrolyte is used as a polymer electrolyte of a secondary sodium ion battery.

Citation Information

Patent Citations

  • Polymer electrolyte prepared by in-situ thermal initiation and all-solid sodium ion battery

    CN110459802A

  • Polar polymer network gel electrolyte and preparation method thereof

    CN115558059A

  • Gel electrolyte for sodium ion battery as well as preparation method and application of gel electrolyte

    CN116722214A

  • Multi-application-field high-rate gel electrolyte and preparation method thereof

    CN116864796A

  • High-pressure-resistant flame-retardant gel polymer electrolyte as well as preparation method and application thereof

    CN118553997A